Prevention of hepatitis B - Marta Estera Kowalska; Paweł Kalinowski; Urszula Jolanta Bojakowska (Journal of Education, Health and Sport, 2017)
Hepatitis B (Hepatitis B) is a hepatitis B virus (HBV) -based liver disease. This virus has an affinity for liver cells, it can cause both acute and chronic viral infections of varying severity. The consequences of chronic HBV infection can be cirrhosis and liver cancer. In Poland in 1989 a preventive program was implemented to reduce HBV infection. Universal vaccinations have been introduced to reduce the prevalence of Type B hepatitis B from 40.3 / 100,000 in 1989 to 7/100 in 2000.